Organization of independent work of the students at study of technical disciplines - Lukyanets, S.V.; Guzov, V.V. (Modern Technique and Technology Conference 2002 (MTT-2002, 2002)
The complex of electronic methodical development which are included in system has the extended functions: 1) allows the teacher to estimate and to set volume of the contents of educational discipline proceeding. from a necessary level of preparation of the engineers - chemists; 2) carries out a role of the methodical teaching aid for the students; 3) allows to raise the requirements to independent work of the students and to carry out the control of their knowledge in a subject.